2023
DOI: 10.3390/genes14040825
|View full text |Cite
|
Sign up to set email alerts
|

Role of Microbiota-Modified Bile Acids in the Regulation of Intracellular Organelles and Neurodegenerative Diseases

Abstract: Bile acids (BAs) are amphiphilic steroidal molecules generated from cholesterol in the liver and facilitate the digestion and absorption of fat-soluble substances in the gut. Some BAs in the intestine are modified by the gut microbiota. Because BAs are modified in a variety of ways by different types of bacteria present in the gut microbiota, changes in the gut microbiota can affect the metabolism of BAs in the host. Although most BAs absorbed from the gut are transferred to the liver, some are transferred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 145 publications
0
9
0
Order By: Relevance
“…Finally, bile acids (BAs) are also linked to autophagy and the maintenance of mitochondrial quality control [109].…”
Section: Brain-gut-liver Axismentioning
confidence: 99%
“…Finally, bile acids (BAs) are also linked to autophagy and the maintenance of mitochondrial quality control [109].…”
Section: Brain-gut-liver Axismentioning
confidence: 99%
“…Bile acids are synthesized from cholesterol. Primary bile acids like chenodeoxycholic acid (CDCA) and cholic acid (CA) are produced first ( 36 ). After production in the liver, primary bile acids are transported by way of the small intestine to the colon where they are metabolized by the gut microbiota into the secondary bile acids such as lithocholic acid (LCA) and deoxycholic acid (DCA) ( 36 ).…”
Section: The Microbiota-gut-brain-immune Interface and Neuroinflammationmentioning
confidence: 99%
“…Primary bile acids like chenodeoxycholic acid (CDCA) and cholic acid (CA) are produced first ( 36 ). After production in the liver, primary bile acids are transported by way of the small intestine to the colon where they are metabolized by the gut microbiota into the secondary bile acids such as lithocholic acid (LCA) and deoxycholic acid (DCA) ( 36 ). These secondary bile acids are then transported across the gut barrier where they may travel to the liver or circulate systemically, likely also crossing the blood-brain barrier ( 36 ).…”
Section: The Microbiota-gut-brain-immune Interface and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that several bile salt hydrolase-containing bacteria, such as Bacteroides spp. , Bifidobacterium, and Lactobacillus , were enhanced in PD patients ( Spichak et al., 2021 ; Ghezzi et al., 2022 ), indicating a complicated association among PD, microbiota, and BAs ( Kiriyama and Nochi, 2023 ), which is still unclear. Wang et al.…”
Section: Pathological Links Between Pd and Gut Microbiotamentioning
confidence: 99%